1997
DOI: 10.1165/ajrcmb.17.3.2861
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lung Vascular and Airway ICAM-1 after Exposure to Bacterial Lipopolysaccharide

Abstract: Airway instillation of bacterial lipopolysaccharide (LPS) into rat lungs induces neutrophil accumulation, which is known to be intercellular adhesion molecule-1 (ICAM-1)-dependent. In the present study, ICAM-1 messenger RNA (mRNA) of whole lung was found to increase by 20-fold in this inflammatory model. This increase was reduced by 81% after treatment of animals with anti-tumor necrosis factor-alpha (TNF-alpha) antibody and by 37% after treatment with anti-interleukin-1 (IL-1) antibody. The same interventions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
95
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 24 publications
8
95
1
Order By: Relevance
“…ICAM-1 has previously been shown to be a requirement for neutrophil recruitment after airway instillation of LPS with peak levels of expression associated with maximum leukocyte adherence (35). In agreement with published data, we found that lung ICAM-1 expression was up-regulated by LPS exposure (24,25). Ebselen dose-dependently abrogated ICAM-1 mRNA expression.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…ICAM-1 has previously been shown to be a requirement for neutrophil recruitment after airway instillation of LPS with peak levels of expression associated with maximum leukocyte adherence (35). In agreement with published data, we found that lung ICAM-1 expression was up-regulated by LPS exposure (24,25). Ebselen dose-dependently abrogated ICAM-1 mRNA expression.…”
Section: Discussionsupporting
confidence: 91%
“…These data suggest that the inhibitory effect of ebselen on LPS-induced neutrophil influx and ICAM-1 expression is partially achieved through an inhibitory effect on IL-1␤. In agreement with an important role of IL-1␤ in this model are the findings showing that an anti-IL-1 Ab reduced LPS-induced lung ICAM-1 mRNA expression, which is necessary for neutrophil recruitment (25).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Perhaps most confusing are the data on gastrointestinal epithelial cells, where the ability of LPS to up-regulate proinflammatory cytokines appears to vary with the cell line tested (67)(68)(69)(70). In addition, airway epithelial cells have demonstrated sensitivity to LPS by NF-B activation, cytokine production, and up-regulation of various defense molecules (71)(72)(73)(74), and LPS has been shown to simulated cytokine expression by human gingival epithelial cells (75)(76)(77). None of these studies identified host cell surface moieties linked to epithelial-LPS interactions.…”
Section: Discussionmentioning
confidence: 99%